Newly isolated alkalophilic Advenella species bioaugmented in activated sludge for high p-cresol removal - Xenofontos, Eleni; Tanase, Anamaria; Stoica, Ileana; Vyrides, Ioannis (My University, 2016)
In this work, an alkalophilic bacterium (LVX-4) capable of using p-cresol as sole source of carbon and energy was screened and isolated from soil polluted by used oil. Phylogenetic (16S rRNA) and phenotypic characterization using Biolog GN microplates and API 20NE strips indicated that LVX-4 strain is a new Advenella species. It showed both the capability to degrade of p-cresol at high concentrations (750. mg/L) and to use p-cresol for growth in a pH from 7 to 10, although the optimum pH was 9. Moreover bioaugmentation of activated sludge with this strain lead to the complete removal of p-cresol in less than 100. h. This is the first study that shows the potential of Advenella sp. to be bioaugmented in activated sludge system for p-cresol biodegradation.
Keywords: Alkalophilic; Bio-augmentation; Biodegradation